Playing sardines - Major, Beverly; Glass, Andrew (New York : Scholastic Inc., 1988)
As soon as they find the hider, neighborhood youngsters squeeze like sardines into one tight spot in this twist on the classic hide-and seek game.
Booklist
2.5
K-3
Keywords: Sardines (Game) -- Fiction; Hide-and-seek -- Fiction; Hide-and-seek -- Fiction